Smart field artillery information system: model development with an emphasis on collisions in Single Sign-On authentication - Manev, Nikola S.; Achkoski, Jugoslav Z.; Petreski, Drage T.; Gocić, Milan Lj.; Rančić, Dejan D. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This paper proposes a model for a Smart Field Artillery Information System (SFAIS) that can be used in a military environment. It is based on Service Oriented Architecture (SOA) and Command, Control, Communications, Computers, and Intelligence Information Systems (C4I), as well as Geographical Information System (GIS) technology. The system aims to contribute in increasing the level of the military’s capacity in the execution of operations in a multinational or a regional environment. In this context, the SFAIS provides a well-designed platform for interoperability with other actors in the same theater of military missions and joint operations. Moreover, the system will be used for educational purposes by being implemented in simulation centers and computer laboratories. This system will provide artillery personnel with proper education which will rely on -  and is going to be conducted in - a simulated  operational environment which will include the whole operational range of the artillery systems used (field of fire) and the process of preparation of the elements as well as conducting the firing in a virtual environment. Additionally,and even more importantly, the probability of collisions in hash functions during Single Sign-on authentication is presented for proving existing security shortcomings in distributed computer systems. Also, studying specific security issues with the SOA based artillery information system emphasizes the significance of applying a military information system in a security environment.
Keywords: Authentication; Single sign-on; GIS; hash function; artillery; Service Oriented Architecture; Security; Military; Information systems